Role balance and team development: A study of team role characteristics under- lying high and low performing teams - Chong, Eric (School of Management Working Papers, 2004)
Research into teams primarily focused on the characteristics of individuals that predispose them to assume certain roles required for team performance. This paper provides an alternative view by defining team characteristics collectively from scores in predefined roles. The characteristics of 33 teams comprising 342 individuals and the teams’ performance in a management simulation are analysed. The results indicate that team roles characteristics defined by creativity, co-ordination and co-operation are positively correlated with team performance. There appears to be no strong relationship between team ‘balance’, measured by the number of team roles represented in a team, and team performance. However, there is a difference in team members’ role behaviours when they are classified into performance groups. These behaviours are associated with the different stages of development a team goes through. The result of this study indicates that amongst more developed teams the Specialist role is associated with better performance. While characteristics associated with the Co-ordinator role are generally positively correlated with performance, this can impede performance of teams that have not reached a certain stage of development.